Early experience with a nutrition and survivorship clinic in esophageal cancer. Issue 2 (22nd June 2020) - Murphy, Conor F; Fanning, Michelle; Raftery, Nicola; Elliott, Jessie A; Docherty, Neil G; Donohoe, Claire L; Ravi, Narayanasamy; le Roux, Carel W; Reynolds, John V
Summary: Improved cure rates in esophageal cancer care have increased focus on health-related quality of life (HRQL) in survivorship. To optimize recovery after esophagectomy, particularly nutritional well-being, a personalized multidisciplinary survivorship clinic was established at this center. Assessments at 6 and 12 months postoperatively include validated European Organization for the Research and Treatment of Cancer (EORTC) symptom and health-related quality of life (HRQL) questionnaires, functional status review, anthropometry, and biochemical screening for micronutrient deficiencies. 75 patients, at a mean age of 63 years, 84% male, 85% with adenocarcinoma, and 73% receiving multimodal therapy were included. Mean preoperative body mass index (BMI) was 27.5 (4.3) kg m −2 . 6- and 12-month assessments were completed by 66 (88%) and 37 (93%) recurrence-free patients, respectively. Mean body weight loss at 6 months was 8.5 ± 6.6% and at 12 months 8.8 ± 7.3%. Of the 12-month cohort, micronutrient deficiency was present in 27 (79.4%) preoperatively and 29 (80.6%) after 1 year ( P = 0.727), most commonly iron deficiency (preoperative: 16 [43.2%] and postoperative: 17 [45.9%] patients, P = 0.100). 26 (70.3%) of these patients also had clinically significant dumping syndrome persisting to 12 months after surgery. We describe a novel follow-up support structure for esophageal cancer patients in the first year of survivorship. This may serve as an exemplar model with parallel application across oncological care.